Overcoming acquired resistance to AZD9291, a third generation EGFR inhibitor, through modulation of MEK/ERK-dependent Bim and Mcl-1 degradation - Shi, Puyu (Clin Cancer Res, 2017)
PURPOSE: The mechanisms accounting for anticancer activity of AZD9291 (osimertinib or TAGRISSO™), an approved third generation EGFR inhibitor, in EGFR-mutant non-small cell lung cancer (NSCLC) cells and particularly for the subsequent development of acquired resistance are unclear and thus are the focus of this study. EXPERIMENTAL DESIGN: AZD9219-resistant cell lines were established by exposing sensitive cell lines to AZD9291. Protein alterations were detected with Western blotting. Apoptosis was measured with annexin V/flow cytomentry. Growth-inhibitory effects of tested drugs were evaluated in vitro with cell number estimation and colony formation assay and in vivo with mouse xenogtaft models. Protein degradation was determined by comparing protein half-lives and inhibiting proteasome. Gene knockdown were achieved with siRNA or shRNA. RESULTS: AZD9291 potently induced apoptosis in EGFR-mutant NSCLC cell lines, in which ERK phosphorylation was suppressed accompanied with Bim elevation and Mcl-1 reduction likely due to enhanced Mcl-1 degradation and increased Bim stability. Blocking Bim elevation by gene knockdown or enforcing Mcl-1 expression attenuated or abolished AZD9291-induced apoptosis. Moreover, AZD9291 lost its ability to modulate Bim and Mcl-1 levels in AZD9291-resistant cell lines. The combination of a MEK inhibitor with AZD9291 restores the sensitivity of AZD9291-resistant cells including those with C797S mutation to undergo apoptosis and growth regression in vitro and in vivo. CONCLUSIONS: Modulation of MEK/ERK-dependent Bim and Mcl-1 degradation critically mediates sensitivity and resistance of EGFR-mutant NSCLC cells to AZD9291 and hence is an effective strategy to overcome acquired resistance to AZD9291.